THE REALITY OF EXTENSION SERVICES PROVIDED TO WORKERS IN THE PRODUCTION OF VEGETABLES ON FARMS BELONGING TO THE HUSSEINIAN AND ABBASIAN HOLY SHRINES IN THE HOLY CITY OF KARBALA - Al-Saedi , A. A. N.; Al-Bdri, A. A. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The research aims to identify the reality of the extension services provided to workers in the vegetable production in the farms of Imam Hussein and Al-Abbas’s shrines by the agricultural and extension departments in the holy Karbala governorate. The research included the vegetable farms belonging to Imam Hussein and Al-Abbas’s holy shrines, as well as the agricultural extension departments that provided extension services to those farms. The research sample was chosen from all the agricultural extension agents in the agricultural extension departments in Karbala governorate, totaling (36) agricultural extension agents. In order to achieve the objectives of the research, the researcher prepared a questionnaire to collect data related to the research topic. It contained a 4-point scale for the reality of extension services provided to workers in vegetable production in the shrine’s farms, which includes (82) paragraphs, to measure the axes of extension services. The research concluded that there are few activities and extension services provided by extension agents in agricultural extension departments. The researcher recommends that the vegetable farms of the two shrines be included in the annual plans to provide activities and extension services by the extension organizations in the governorate. Besides that, these activities should be planned and targeted..